2003
DOI: 10.1002/cncr.11376
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of neuroendocrine differentiation and hormone production in patients with Stage I nonsmall cell lung carcinoma

Abstract: Chiral dirhodium carboxylate complexes ([Rh2(S‐PTAD)4] or [Rh2(S‐PTTL)4], see scheme) efficiently catalyze asymmetric three‐component coupling reactions of α‐diazophosphonates, anilines, and electron‐deficient aldehydes to give α‐amino‐β‐hydroxyphosphonates. The high level of enantiocontrol provides evidence for the intermediacy of metal‐bound ammonium ylide in the product‐forming step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
3
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 60 publications
4
63
3
2
Order By: Relevance
“…Predominantly mixed-type adenocarcinomas, 40 three acinar adenocarcinomas, one solid mucin producing adenocarcinoma and one bronchioloalveolar (BA)/lepidic mucinous adenocarcinoma/mucinous adenocarcinoma in situ were studied to validate the different patterns. Forty-two cases (93.3%) with acinar pattern (being the most prevalent), Thirteen cases (28.9%) showed lymph node metastasis as follows: acinar pattern was present in 13 cases (100%); solid and micropapillary patterns were present in 3 cases each (23%); and papillary pattern in 2 cases (15.4%).…”
Section: Resultsmentioning
confidence: 99%
“…Predominantly mixed-type adenocarcinomas, 40 three acinar adenocarcinomas, one solid mucin producing adenocarcinoma and one bronchioloalveolar (BA)/lepidic mucinous adenocarcinoma/mucinous adenocarcinoma in situ were studied to validate the different patterns. Forty-two cases (93.3%) with acinar pattern (being the most prevalent), Thirteen cases (28.9%) showed lymph node metastasis as follows: acinar pattern was present in 13 cases (100%); solid and micropapillary patterns were present in 3 cases each (23%); and papillary pattern in 2 cases (15.4%).…”
Section: Resultsmentioning
confidence: 99%
“…13 Therefore, Merkel cell carcinoma seems to occupy an intermediate position between cutaneous squamous cell carcinoma and extracutaneous small cell carcinoma, so that Merkel cell carcinoma is much more aggressive than the former but less so than the latter. [2][3][4][5] Neuroendocrine differentiation is considered to carry a negative prognostic connotation in some carcinomas, 15 whereas other carcinoma types have yielded contradictory results 16,17 or shown just a trend toward an association between neuroendocrine differentiation and high tumor grade. 18 We found a statistically significant association of low (o10% of tumor cells) expression of synaptophysin with good outcome in Merkel cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…This report focuses on NE cells found in lung tumors and the NE-differentiation process. NSCLC that contain foci of NE cells constitute 10-35% of all NSCLC and have been proposed to be an intermediary step between NSCLC and SCLC (Graziano et al, 1994;Linnoila et al, 1994;Gosney et al, 1995;Pelosi et al, 2003). Thus, the NE differentiation of NSCLC represents an excellent model for understanding the regulatory aspects of NE differentiation in lung cancer and thus the identification of key regulatory proteins for therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…In more recent studies, that correlation now seems less well defined (Jiang et al, 1999;Graziano et al, 2001;Yesner, 2001;Gajra et al, 2002). Nevertheless, recent studies using more defined NSCLC specimens demonstrated that stage I adenocarcinomas with more than 5% NE tumor cells are clinically aggressive tumors, and hormone production identifies a more fully developed NE phenotype but is not relevant to prognosis (Pelosi et al, 2003). Therefore, it seems more likely that study of a subset of NE-like differentiated NSCLC, delineated using NE markers as part of a more global determination scheme, can still be useful.…”
Section: Discussionmentioning
confidence: 99%